Identification of Extracellular Matrix Components and Biological Factors in Micronized Dehydrated Human Amnion/Chorion Membrane - Lei, Jennifer (Adv Wound Care (New Rochelle), 2017)
Objective: The use of bioactive extracellular matrix (ECM) grafts such as amniotic membranes is an attractive treatment option for enhancing wound repair. In this study, the concentrations, activity, and distribution of matrix components, growth factors, proteases, and inhibitors were evaluated in PURION(®) Processed, micronized, dehydrated human amnion/chorion membrane (dHACM; MiMedx Group, Inc.). Approach: ECM components in dHACM tissue were assessed by using immunohistochemical staining, and growth factors, cytokines, proteases, and inhibitors were quantified by using single and multiplex ELISAs. The activities of proteases that were native to the tissue were determined via gelatin zymography and EnzChek(®) activity assay. Results: dHACM tissue contained the ECM components collagens I and IV, hyaluronic acid, heparin sulfate proteoglycans, fibronectin, and laminin. In addition, numerous growth factors, cytokines, chemokines, proteases, and protease inhibitors that are known to play a role in the wound-healing process were quantified in dHACM. Though matrix metalloproteinases (MMPs) were present in dHACM tissues, inhibitors of MMPs overwhelmingly outnumbered the MMP enzymes by an overall molar ratio of 28:1. Protease activity assays revealed that the MMPs in the tissue existed primarily either in their latent form or complexed with inhibitors. Innovation: This is the first study to characterize components that function in wound healing, including inhibitor and protease content and activity, in micronized dHACM. Conclusion: A variety of matrix components and growth factors, as well as proteases and their inhibitors, were identified in micronized dHACM, providing a better understanding of how micronized dHACM tissue can be used to effectively promote wound repair.